The Role of Acehnese Women in Post-Conflict Local Economic Development in North Aceh Regency - Richa Meliza; Ade Ikhsan Kamil; Mujiburrahman Mujiburrahman; Aflia Riski; Rizki Yunanda; Shah Diva Nazwa Ramadhani; Galang Bayhaqie (LPPM Universitas Malikussaleh, 2024)
This research focuses on the role of Acehnese women in post-conflict local economic development in North Aceh. Aceh is an area that has a long history of armed conflict, especially those related to the Free Aceh Movement (GAM) and the Indonesian government. This conflict lasted for more than three decades, which not only resulted in casualties, but also destroyed infrastructure, affected economic stability, and changed the social dynamics of Acehnese society. On this basis, this study seeks to identify what women experience, their strategies, structural and cultural barriers and their experiences in the local economy after conflict. Data collection is carried out through Live in, observation, in-depth interviews and the use of documents. The results of the study show that women in North Aceh play an important role in post-conflict economic development, driving the agriculture, micro enterprises, and handicraft sectors. They are active in the economic empowerment of families and communities, despite the challenges of accessing capital and education. Skills training programs help women increase their entrepreneurial capacity. In addition, they also play a role in post-conflict social reconciliation, improving intergroup relations, and fighting for women's rights in the peace process. Despite much progress, they still face difficulties in accessing education and gender equality in the job market.